The Forming Analysis of SCM440 Alloy Steel Hexagon Head Flange Bolts - Yang, Chih-Cheng; Nguyen, Hong Quy; Wang, Kuo-Hsiang (European Journal of Applied Sciences, 2023)
In this study, a multi-stage cold forming process for the manufacture of hexagon head flange bolts is studied numerically with SCM440 alloy steel. The cold forming process through five stages includes forward extrusion, two upsetting operations, hexagonal trimming and circular trimming. The numerical study of cold forming is conducted using the code of DEFORM-3D. The formability of the workpiece is studied, such as the effect on forming force responses, maximum forming forces, effective stress and strain distributions and metal flow pattern. In the five-stage forming process, in the two upsetting and one hexagonal trimming forming stages, the effective stresses in the head of the workpiece are significantly high, and the effective strains are also significantly high due to large deformation. The flow line distributions are also very complex in which the flow lines in the trimming region of the upset head are severely bent, highly compacted, and eventually fractured due to excessive trimming. For the maximum axial forming force, the fourth stage, which the head of the workpiece is heavily trimmed into a thick hexagonal shape, is 1,360.4kN which is the largest among the five stages due to the large amount of trimming. However, for the forming energy, the second stage, which the workpiece is upset into a conical shape, is 9,841.0J which is the largest among the five stages due to longer acted axial forming stroke. The total maximum axial forming forces from the first to the last stages are 3,608.8kN and the total forming energies are about 26.16kJ.